Strategi Viral Marketing Melalui Instagram @Suweger.Indonesia Dalam Membangun Brand Awareness - Wahyuning M., Diana Nur; Tranggono, Didiek (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to describe how a viral marketing strategy can occur on the Instagram account @suweger.indonesia and how the viral marketing activities carried out can build brand awareness. Considering that after the pandemic, people's interest in consuming modern drinks has increased, however, a large number of competitors in the city of Surabaya has made the business competition even tougher, therefore a strategy is needed to build brand awareness. This research is descriptive qualitative research, where the data collection method is through in-depth interviews, observation, and documentation. The informants were selected based on a purposive sampling technique consisting of key informants, namely the Human Resources Officer and Marketing Manager of Suweger Indonesia, the main informant, namely the Content & Social Media Officer who manages Instagram Suweger Indonesia and supporting informants, namely five Instagram followers @Suweger.Indonesia. The results of this study indicate that Suweger Indonesia uses a viral marketing strategy by implementing a viral marketing component. Meanwhile, Suweger Indonesia's marketing messages were analyzed based on the viral marketing dimension which influences a person's attitude in spreading the message, showing that the majority of supporting informants liked the messages shared by Suweger Indonesia. In addition, Suweger Indonesia also utilizes viral marketing elements so that the viral marketing activities carried out can be more effective. Based on supporting informant data, the viral marketing activities carried out by Suweger Indonesia have made the public aware of the Suweger Indonesia brand. Keywords: Viral Marketing; Instagram; Brand Awareness